Efikasi Oxytetracycline Terhadap Kesehatan Ikan Lele yang Diinfeksi Bakteri Edwardsiella tarda - A'yunin, Qurrota; Kartikaningsih, Hartati; Andayani, Sri; Arifin, Nasrullah Bai (JFMR (Journal of Fisheries and Marine Research), 2019)
Edwardsielliosis is a disease that commonly infects freshwater fish including catfish (Clarias sp). Edwardsielliosis is caused by Edwardsiella tarda infection and causes mass mortality in catfish farming. Overcoming diseases in freshwater fish can use drugs or antibiotics that are classified as safe and their use is in accordance with government regulations. This study aims to determine the appropriate dosage of Oxytetracycline in catfish infected by E. tarda bacteria through histological analysis. The study design used Completely Randomized Design with 3 treatments, 1 control and 3 replications in each treatment. Catfish used were Â± 25 cm in size and the dose of oxytetracycline used were 15, 30, and 45 ppm. The results showed tissue damage edema, vacuolization, necrosis, and haemorhage in fish infected with Edwardsiella tarda bacteria with the lowest damage at 45 ppm of oxytetracycline treatment. The results indicate that oxytetracycline has an effect on muscle histology and recovery of fish health.